Resilience of young athletes depending on the individual or collective character of their practice - Zubizarreta-Cortadi, A.; Arribas-Galagarraga, S.; Luis de Cos, I. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The objective of this study was to determine the levels of resilience with its two dimensions, “acceptance of self and life" (AUM) and "individual competence" (CP), in individual and collective sports participants. Comparisons depending on competitive level and sex, as well as, intragroup and intergroup comparisons were performed. A total of 435 athletes (300 men and 135 women) completed a socio-demographic questionnaire and the Resilience Scale (Wagnild and Young, 1993). The results indicate that those who practise individual sports obtain average values of resilience and the CP dimension higher than those obtained by athletes who do so collectively (p < 0.005). According to sex, in the AUM dimension, girls have lower averages than boys (p< 0.005). As for the competitive level, the trend is that at a higher competitive level, higher average resilience score (p < 0.05). The results draw the image of the athlete resilient as a young boy practicing sport of individual character and high level competitive.